2016
DOI: 10.1007/978-1-4939-6728-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Platelet-Derived Extracellular Vesicles

Abstract: Platelets participate in several physiological functions, including hemostasis, immunity, and development. Additionally, platelets play key roles in arterial thrombosis and cancer progression. Given this plethora of functions, there is a strong interest of the role of platelet-derived (extracellular) vesicles (PDEVs) as functional mediators and biomarkers. Moreover, the majority of the blood-borne EVs are thought to originate from either platelets or directly from the platelet precursor cells, the megakaryocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In fact, the formation of these clumps or aggregates probably explains why previously, on relative insensitive flow cytometers, mainly "EVs" of platelet origin were measured [2,15]. Given the fact that recent evidence suggests that the bulk of small EVs cannot be pelleted from plasma or serum by (ultra) centrifugation supports the idea that residual platelets rather than platelet-derived EVs explained these earlier observations [8].…”
Section: Discussionmentioning
confidence: 86%
“…In fact, the formation of these clumps or aggregates probably explains why previously, on relative insensitive flow cytometers, mainly "EVs" of platelet origin were measured [2,15]. Given the fact that recent evidence suggests that the bulk of small EVs cannot be pelleted from plasma or serum by (ultra) centrifugation supports the idea that residual platelets rather than platelet-derived EVs explained these earlier observations [8].…”
Section: Discussionmentioning
confidence: 86%
“…Negative selection with magnetic beads was performed for preparation of Exos‐depleted CM (EDCM) considering its relatively negligible effect on the remaining components of CM after magnetic bead‐based Exos depletion. [ 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that upon activation, blood platelets are able to release two types of EVs, i.e., microparticles and exosomes [34,35] . Platelet-derived microparticles (also referred to microvesicles) are characterized by an average of the size of 70-100 nm and the PS presentation at their surface, which mediates their capabilities in coagulation and thrombosis [36] . On contrary, platelet-derived exosomes are characterized by their small size (< 80 nm) and the presence of CD63 antigen, which is known as the tetraspanin that belongs to the transmembrane 4 superfamily, while larger vesicles (> 0.5 µm) containing chromatin materials are referred to apoptotic bodies [35,36] .…”
Section: Platelet-derived Vesiclesmentioning
confidence: 99%